Calidad de la gasolina regular de Costa Rica entre los años 2006-2010 - Bazán Salazar, Víctor (2018)
This study explores the behavior and evolution on the quality of motor regular gasoline distributed in Costa Rica during the 2006-2010 period. Traditionally, fuel behavior studies are done on univariate and bivariate statistical methods but fail to provide sufficient information to describe the relationship between the attributes and multidimensionality of the regular gasoline’ behavior information. To overcome this limitation, a Principal Component Analysis (PCA) is performed using the data gathered during the five years of the study. Additionally, an automatic classification by an ascending hierarchical classification was performed to determine the behavior of regular gasoline when forming groups with similar characteristics. Based on the analysis, it is found that regular gasoline evolves toward a better fuel within the current regulations, but this evolvement it's done in a oscillatory manner during the study period, where the main improvement is the reduction in olefins content in the fuel.